ANALISIS KEGIATAN PENDATAAN KELUARGA PROGRAM INDONESIA SEHAT DENGAN PENDEKATAN KELUARGA DI PUSKESMAS KOTA SEMARANG (Studi Kasus pada Puskesmas Mijen) - Eri Virdasari; Septo Pawelas Arso; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2018)
Death in Indonesia is dominated by Non-Communicable Diseases and Communicable Diseases.Program Indonesia Sehat dengan Pendekatan Keluarga is one of the Puskesmas's efforts to improve health services.The initial step of PIS-PK is family data collection. Semarang is one of the regions that has collected data on PIS-PK families with 6 special location. Puskesmas Mijen is one of the Puskesmas with the lowest data coverage. This study aims to analyze the implementation of family data collection activities seen from input, process, and output.This research is a qualitative research method with in-depth interviews with 17 informants, as well as observing the aspects of input, process, and output. The results of the research on the input variables indicate that the availability of personnel is sufficient, but constrained in the competence and workload of officers, funds, infrastructure, and the use of policies.The process variable shows that the implementation is not in accordance with the guidelines or plans, because the socialization is not evenly distributed, the distribution of tasks is not appropriate, and unscheduled supervise.In the output variable, the implementation is not in accordance with the predetermined schedule and target. Family data collection activities are still 69% of the 100% target.However, these results have been good enough because the Puskesmas has carried out activities with limited resources. Suggestions for the Semarang City Health Office are scheduled monitoring and evaluation.Puskesmas could immediately utilizes PIS-PK data as material for program planning, conducting cross-sector socialization and coordination, and procuring supporting infrastructure for family data collection activities.